PEMANFAATAN LIMBAH TIMBUNAN LEMAK ABDOMEN IKAN PATIN - RTM Sutamihardja; Ratna Fatmasari; Vieriya Devi; Padmono Citroreksoko (Jurnal Ecolab, 2008)
Fishery industries of ikan patin (Pangasius hypothalamus) has increasing steadily through the prospect of highprice. The portion of the fish is used just only the meat part, but the head and abdomen of the fish portion werethrown away regarded as a waste. The purpose of the study was tried to seek the content and composition of thewaste part of the fish abdomen containing accumulation of fat, especially for the polyunsaturated fatty acids(PUFA) so the potency of PUFA as an essential nutrient.The abdomen fish fat was analyzed for its water content, fat content, iod value, separation of the fat by thin layerchromatography, and the content and composition of fatty acid by gas chromatography. The content and compositionsof the fish fat were as followed: oleic fatty acid as mono unsaturated fatty acid (MUFA) was 44,13%, linoic acidas PUFA was 19,01%, and palmitic acid was 22,14%. For further uses each fatty acid can be separated throughfractionation according to its various temperature and its melting point.